Characteristics, Fertility, And Mortality Of The Population In Teluk Bintuni Regency, West Papua Province - Warami, Hugo; Lenny Marit, Elisabeth (International Journal of Educational Research & Social Sciences, 2022)
This article aims to reveal the characteristics, fertility, and mortality of the population in Teluk Bintuni Regency, West Papua Province. This study applies two approaches, namely (1) a theoretical approach and (2) a methodological approach. The theoretical approach is an exploration of the sociological theory of fertility (Davis and Blake, 1974) and the economic theory of fertility (Becker, 1976), while the methodological approach is a descriptive approach with an explanative dimension. Based on a demographic perspective, this research applies scientific principles to population data, as well as adapts the steps of scientific studies in other fields of science. This study follows the procedures of (1) providing data, (2) analyzing data, and (3) presenting the results of data analysis. The data used in this study are derived from primary data and secondary data. Primary data are in the form of data derived from the results of the Census of Indigenous Papuans (OAP) of Teluk Bintuni Regency, which was conducted by the author in 2019, and secondary data, which are derived from the data published by the Central Statistics Agency (BPS) of West Papua Province and Teluk Bintuni Region. This article focuses on the efforts to reveal the “Characteristics, Fertility, and Mortality of the Population in Teluk Bintuni Regency, West Papua Province”.